2021
DOI: 10.1021/acs.jpcc.1c04368
|View full text |Cite
|
Sign up to set email alerts
|

Structural Inhibition of Silver Surface Oxidation

Abstract: Surface structure and oxidation are key to silver-based heterogeneous catalysis. Prevention of surface reconstruction may favor electrophilic oxygen, which is believed to be the active species in silver-catalyzed oxidation. To determine whether terrace width or step geometry enables control of oxidation and concomitant reconstruction, we investigated oxidation of the topmost layer of a curved Ag(111) crystal. This crystal contains a range of terrace widths having either A- or B-type step geometries. Atomic oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Dissociative adsorption on Cu(111) and vicinals occurs preferentially on step edges and kink defects. ,, Small defect islands rapidly oxidize to form triangular islands that grow with O 2 exposure. A very similar oxidation mechanism was shown to occur on silver using a c -Ag­(1 1̅1)[110] R 31° crystal. , Our current RAIRS results indicate that the remaining nonoxidized Cu(111) patches after partial oxidation of the surface are electronically unperturbed, because the center of the CO band frequency does not change. We only find that the clean Cu(111) area decreases with increasing O 2 exposure.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Dissociative adsorption on Cu(111) and vicinals occurs preferentially on step edges and kink defects. ,, Small defect islands rapidly oxidize to form triangular islands that grow with O 2 exposure. A very similar oxidation mechanism was shown to occur on silver using a c -Ag­(1 1̅1)[110] R 31° crystal. , Our current RAIRS results indicate that the remaining nonoxidized Cu(111) patches after partial oxidation of the surface are electronically unperturbed, because the center of the CO band frequency does not change. We only find that the clean Cu(111) area decreases with increasing O 2 exposure.…”
Section: Discussionsupporting
confidence: 69%
“…A very similar oxidation mechanism was shown to occur on silver using a c -Ag(1 1̅1)[110] R 31° crystal. 58 , 59 Our current RAIRS results indicate that the remaining nonoxidized Cu(111) patches after partial oxidation of the surface are electronically unperturbed, because the center of the CO band frequency does not change. We only find that the clean Cu(111) area decreases with increasing O 2 exposure.…”
Section: Discussionmentioning
confidence: 66%
“…Ag(111). 34,35 The growth of the oxide patches reduces remaining clean Cu(111) surface area that binds post-dosed CO. The CO is otherwise unaffected as evidenced from the exact same internal stretch frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The elemental pro les of Ag and O across the surface, obtained from energy dispersive X-ray spectroscopy (EDX) analysis (Fig. 1f), suggested that the chemical purity of Ag was well preserved up to the topmost surface layer of the at Ag lm and did not exhibit surface oxidation 27 .…”
Section: Structure and Strain Analysis Of Single-crystal Ag Films Wit...mentioning
confidence: 99%